Distribution of heavy metals profile in groundwater system at solid waste disposal site - Samuding, K. (2009)
This paper presents the distribution of heavy metals profile in groundwater system at solid wastedisposal site in Taiping, Perak. In this study, six boreholes were constructed within the solidwaste disposal site. Soil samples were collected from depths between 1 and 30 m below groundsurface (bgs) at 1 m intervals during the construction of the boreholes with a down-hole hammer in alluvial deposits. Pore water content of the samples was extracted in order to determine theconcentrations of heavy metals suc as lead (Pb), zinc (Zn), cadmium (Cd), iron (Fe), manganese(Mn), and chromium (Cr). In this study, surfer software was used to plot the contouring of heavy metals concentration. From the profiling plot, the highest concentrations peaks most of the heavymetals are seen at borehole TP6 and and can be detected up to 25 m below ground surface (bgs).Most of the heavy metals concentration were exceeded the maximum permissible concentration(MPC) as specified in the WHO Standard for Drinking Water. Based on contour diagrams, thedistribution of heavy metals were localized and confined within the dumping area and not diffused and dispersed over a wide area. These results play an important role in order todetermine and visualize the locations, which are affected with the leachate plume. Hence, theseresults can help the local authorities to take an action in term of remediation purposes.